Waqf fundraising management: a conceptual comparison between traditional and modern methods in the waqf institutions - Shulthoni, Muhammad; Md Saad, Norma (State Institute of Islamic Studies (IAIN) Salatiga, 2018)
This paper focuses on the traditional and modern theoretical models of funding for Islamic philanthropy, especially waqf (endowment). One of the greatest challenges for the sustainability of waqf institution is the ability to mobilize fund that will develop the institution to expand and grow. There is no short cut or magic way in fundraising, and the management team will need to evaluate and assess which options are beneficial to the awqāf institutions. Finally, this paper will hopefully contribute to waqf fundraising management in Muslim as well as other countries.